Music-based language programme teacher training on preschool teachers’ music teaching self-efficacy and delivery performance: A case study - Sim, TeeNa; Lee, Julia Ai Cheng (Southeast Asia Early Childhood Journal, 2024)
Music substantially impacts early childhood development, especially language development, yet early childhood policies rarely emphasise the role of music in early learning and engagement. Research shows that effective delivery of early childhood music programmes depends on teachers' music knowledge, skills, and music teaching self-efficacy, which may be enhanced through teacher training. However, little is known about the training details and preparation of non-music-specialist preschool teachers who use music to teach. The present study sought to determine whether music-based language programme (MBLP©) teacher training could improve the music teaching self-efficacy of non-music specialist preschool teachers and their MBLP© delivery in an inclusive preschool classroom. The 14 training sessions consist of a briefing, a workshop, a practicum, interactive reflections, and observations. Three non-music-specialist preschool teachers were trained to deliver MBLP© lessons to nine preschoolers aged 33–47 months. The within-subjects design investigated the teachers' self-efficacy in music teaching, while the single-subject design tracked their MBLP© lesson delivery performance. Data was collected using a self-reported music background survey, pre-, mid-, and post-test music teaching self-efficacy, teachers' feedback, and MBLP© lesson observations. The results showed that the training increased music teaching self-efficacy by 10–46% and revealed a positive relationship between practicum with interactive reflections and lesson delivery performance. The findings suggest that providing MBLP© training to non-specialist preschool teachers could help address language developmental issues in inclusive preschool settings.